Addressing the Shortage of Health Professionals in Rural China: Issues and Progress; Comment on "Have Health Human Resources Become More Equal between Rural and Urban Areas after the New Reform?" - Jianlin Hou; Yang Ke (Kerman University of Medical Sciences, 2015)
Maldistribution of health professionals between urban and rural areas has been a serious problem in China. Urban hospitals attract most of the health professionals with serious shortages in rural areas. To address this issue, a number of policies have been implemented by the government, such as free medical education in exchange for obligatory rural service.